Experiments on neoclassical asymmetric superbanana ripple transport in electron plasma - Kabantsev, A.A.; Driscoll, C.F. (Національний науковий центр «Харківський фізико-технічний інститут» НАН України, 2010)
Ripples in magnetic or electrostatic confinement fields give rise to trapping separatrices, and the conventional neoclassical helical ripple transport describes phenomena coming from the collisional trapping/detrapping of particles in the helical ripple wells. Our experiments and novel theory have now characterized a new kind of neoclassical transport processes arising from chaotic (collisionless) separatrix crossings, which occur due to equilibrium E×B plasma rotation along poloidally asymmetric (ruffled) separatrices, and due to wave-induced separatrix modulations.